PENGARUH EUROPEAN CONVENTION OF HUMAN RIGHTS (ECHR) SEBAGAI REZIM HAM DI EROPA (TELAAH MELALUI PENDEKATAN REGIME-INTERPLAY) [THE INFLUENCE OF THE EUROPEAN CONVENTION OF HUMAN RIGHTS (ECHR) AS A HUMAN RIGHTS REGIME IN EUROPE: AN ANALYSIS OF A REGIME-INTERPLAY APPROACH] - Herry Wahyudi (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2020)
The issue of human rights is a problem of great concern in the European Union.  Previous alliances faced problems related to human rights in the areas of geopolitics and geo-economics.  The ECHR (European Convention of Human Rights) is present as a regime carrying out human rights values that were previously influenced by COE (The Convention of Europe) in the European Union. The development of the ECHR as a human rights regime in the European Union is very dependent on the conditions of the EU member states themselves, which were previously fragmented into fascist and communism systems and must be transformed into democratic liberals. Data in this research will be explored through literature method (library research). The process of developing the ECHR as a human rights regime should be analyzed through an international regime approach using the theory of regime-interplay which will examine the ECHR process as  one of the influential human rights regimes in the European Union.Bahasa Indonesia Abstract: Isu Hak Asasi Manusia adalah masalah yang sangat diperhatikan di Uni Eropa. Aliansi negara-negara Eropa sebelumnya menghadapi masalah yang berkaitan dengan Hak Asasi Manusia yang dihubungkan dengan aspek geo-politik dan geo-ekonomi di kawasan tersebut. ECHR (Konvensi Eropa tentang Hak Asasi Manusia) hadir sebagai rezim yang menjalankan nilai-nilai HAM yang sebelumnya dipengaruhi oleh COE (Konvensi Eropa) di Uni Eropa. Perkembangan ECHR sebagai rezim hak asasi manusia di Uni Eropa sangat tergantung pada kondisi negara-negara anggota UE sendiri, yang sebelumnya terfragmentasi menjadi sistem fasisme dan komunisme, dan harus ditransformasikan menjadi sistem liberal. Data dalam penelitian ini akan dianalisa melalui metode literatur (studi pustaka). Proses pengembangan ECHR sebagai rezim Hak Asasi Manusia dianalisis melalui pendekatan rezim internasional menggunakan teori regime-interplay yang akan menelaah proses ECHR sebagai salah satu rezim HAM yang berpengaruh di Uni Eropa.